The Legal Implications of the Altman Z-Score as a Tool for Bankruptcy Prevention Through the Case Study of PT. Sri Rejeki Isman Tbk (Sritex) - Doloksaribu, Samuel Baringin (UI Scholars Hub, 2025)
Indonesia’s bankruptcy law, as regulated by Law No. 37 of 2004, allows debtors to be declared bankrupt based solely on the existence of two creditors and one unpaid debt, without requiring a substantive assessment of their financial health, raising concerns about fairness, legal certainty, and economic impact. This thesis investigates whether predictive financial models such as the Altman Z-Score can be integrated into Indonesia’s legal framework to improve early detection and prevention of corporate insolvency. The central question is how these models can be legally recognized and implemented, and what challenges or reforms are necessary to facilitate their use. Employing a normative juridical method and comparative study with jurisdictions like Germany, the UK, and Singapore, the research finds that financial models could have foreseen cases like PT Sritex’s bankruptcy and enabled earlier intervention. The study concludes that integrating such models would create a more balanced, preventive, and transparent bankruptcy process, while recommending specific regulatory and institutional reforms.